If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying cos(x) + cos(3x) = 2sen(6x) * cos(x) Multiply cos * x cosx + cos(3x) = 2sen(6x) * cos(x) Remove parenthesis around (3x) cosx + cos * 3x = 2sen(6x) * cos(x) Reorder the terms for easier multiplication: cosx + 3cos * x = 2sen(6x) * cos(x) Multiply cos * x cosx + 3cosx = 2sen(6x) * cos(x) Combine like terms: cosx + 3cosx = 4cosx 4cosx = 2sen(6x) * cos(x) Remove parenthesis around (6x) 4cosx = 2ens * 6x * cos(x) Reorder the terms for easier multiplication: 4cosx = 2 * 6ens * x * cos * x Multiply 2 * 6 4cosx = 12ens * x * cos * x Multiply ens * x 4cosx = 12ensx * cos * x Multiply ensx * cos 4cosx = 12cenos2x * x Multiply cenos2x * x 4cosx = 12cenos2x2 Solving 4cosx = 12cenos2x2 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12cenos2x2' to each side of the equation. -12cenos2x2 + 4cosx = 12cenos2x2 + -12cenos2x2 Combine like terms: 12cenos2x2 + -12cenos2x2 = 0 -12cenos2x2 + 4cosx = 0 Factor out the Greatest Common Factor (GCF), '4cosx'. 4cosx(-3ensx + 1) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'cosx' equal to zero and attempt to solve: Simplifying cosx = 0 Solving cosx = 0 Move all terms containing c to the left, all other terms to the right. Simplifying cosx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-3ensx + 1)' equal to zero and attempt to solve: Simplifying -3ensx + 1 = 0 Reorder the terms: 1 + -3ensx = 0 Solving 1 + -3ensx = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3ensx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3ensx = 0 + -1 -3ensx = 0 + -1 Combine like terms: 0 + -1 = -1 -3ensx = -1 Add '3ensx' to each side of the equation. -3ensx + 3ensx = -1 + 3ensx Combine like terms: -3ensx + 3ensx = 0 0 = -1 + 3ensx Simplifying 0 = -1 + 3ensx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 | | 9x-2=5x+8 | | 5x-10xy=5(x-2y) | | 5x-4=10y | | 2x+9=5x+54 | | 2x+15=x+16 | | 5/9+2/9= | | -6-2(m+4)=36 | | 3y-11=2y-6 | | 4x-5(2x+1)=7x+3(4x-5) | | 3/2-2/7= | | x+x+x+2=3+2x | | 4.9-5.2=4.7 | | x+x+x+2=3x+2 | | 0=80x-x | | 7x-6=3x+54 | | 4d+6+2d=6(d+6) | | -6x-12+8x-21=-6 | | x*1.012048193=84 | | -3x+11+5x+17=4 | | (4x-5)(2x+1)=0 | | 2(3d+3)=4d+6+2d | | 84y-1*y=84 | | 1.9x+2.4=8.9 | | 5x-x=10-2y |